TINGKAT PENGARUH STRATEGI PEMASARAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA PDAM KABUPATEN SOPPENG - Muzakkir, Muzakkir; Rosdiana, Andi; Arya, Dandi; Syadaruddin, Andi; Yusri, Yusri (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of marketing strategy and service quality on customer satisfaction at the Soppeng Regency Regional Water Company (PDAM). In this context, customer satisfaction is a crucial factor influencing the company's sustainability and reputation. The data used in this study are quantitative, analyzed using multiple regression using the Statistical Package for Social Science (SPSS). Primary data collection was conducted through questionnaires distributed to 60 respondents to determine the influence of each variable, both partially and simultaneously, on customer satisfaction. The results of the study indicate that a) the marketing strategy variable has a significant positive effect on customer satisfaction; b) the service quality variable also has a significant positive effect on customer satisfaction; and c) simultaneously, both variables have a positive and significant effect on customer satisfaction at the PDAM in the Botto sub-district, Lalabata District, Soppeng Regency. The results of this study indicate that to improve customer satisfaction, it is necessary to utilize social media as a more effective communication platform for interacting with customers. It is also necessary to develop a more effective and responsive customer complaints system that can respond quickly to customer complaints, provide satisfactory solutions, and support continuous improvement in service.